Human Capital and Regional Growth Perspective - Golejewska, Anna (Regional Barometer. Analyses & Prognoses, 2013)
Accumulation of human capital is one of the major determinants of economic growth. In the last decades, theoretical and empirical literature has analysed this issue at regional level, providing interesting results. The analysis focuses on 35 regions of the Visegrad Group (NUTS 2 level) in 2002–2009 and is based on Eurostat Regional Statistics. The objective was to compare competitiveness and human capital intensity in the Visegrad Group regions, verify the existence of correlation and thus potential human capital growth effects. The analysis comprised two groups of indicators: measures of competitive position and human capital education indicators, as measures of competitive ability. The results showed that there have been and continue to be substantial differences among the regions as regards competitiveness and human capital. According to the correlation results, one can suppose — following the research assumptions — that human capital could have positive impact on regional competitiveness in the Visegrad countries in 2002–2009. However, one cannot forget that the relation between wealth and human capital can be reverse. Level of wealth and structure of the regional/local economy could affect the level and quality of human capital. Regardless of this, in the case of Visegrad Group regions, further econometrical research is still needed.